The Effectiveness Of Inquiry-Based Learning In Improving Students’ Biology Achievement - Nurapipah; Pardiyansah; Eko Wulandari (Journal of Global Educational Perspectives, 2026)
This study aims to investigate the effectiveness of Inquiry-Based Learning (IBL) in improving students’ biology achievement. A quasi-experimental research design was employed, involving two groups: an experimental group taught using Inquiry-Based Learning and a control group taught using conventional methods. The sample consisted of senior high school students selected through purposive sampling. Data were collected using pre-test and post-test instruments to measure students’ learning outcomes. The results revealed that there was no significant difference between the two groups in the pre-test, indicating similar initial abilities. However, the post-test results showed that the experimental group achieved significantly higher scores than the control group. Statistical analysis using an independent samples t-test confirmed that the difference was significant at the 0.05 level. The findings indicate that Inquiry-Based Learning has a positive effect on students’ biology achievement. Additionally, students in the experimental group demonstrated higher engagement, motivation, and critical thinking skills during the learning process. Despite some initial challenges in implementation, Inquiry-Based Learning proved to be an effective instructional strategy. Therefore, it is recommended that educators adopt this approach to enhance biology learning outcomes.